P179 How do inpatients compare with outpatients when investigating iron deficiency anaemia?. (19th June 2022) - Masterman, Benjamin; Saunsbury, Emma; Perry, Rachel
Abstract : Introduction: Iron deficiency anaemia (IDA) has many potential causes which become more prevalent with age and comorbidity. The current study asks whether inpatients, with their high level of age and comorbidity, are less likely to find a bleeding point or malignancy at endoscopy than their outpatient counterparts. Methods: Inpatient referrals to a single gastroenterology department were retrospectively reviewed, with those relating to IDA analysed further. Electronic health records were used to obtain data on comorbidities, biochemistry and results from endoscopic and radiological investigations. An outpatient cohort was developed from the same hospital in a similar fashion. Statistic tests were primarily chi 2, t-test and logistic regression, all using Stata V16 (StataCorp). Results: 196 outpatient and 178 inpatient referrals were included. Inpatients were shown to have higher average age and level of comorbidity and lower average haemoglobin and eGFR. Inpatients were less frequently investigated with CT colonography and colonoscopy (p<0.001, Figure 1 ), adjusting for this in regression analysis had no impact on the primary outcomes. Inpatients had OR 2.51 (95%CI 1.44, 4.37; p=0.001) for significant bleeding point and OR 0.55 (95%CI 0.23, 1.31; p=0.178) for GI malignancy. Splitting findings into UGI and LGI, inpatients had OR 5.75 (95%CI 2.52, 13.11; p<0.001) UGI bleeding and OR 0.33 (95%CI 0.12, 0.91; p<0.001) LGI bleeding. Mortality rate ratio was significantly higher in inpatients at 4.73 (95%CI 2.70, 8.28; p<0.001). Conclusions: Demographic differences between cohorts are highlighted, likely influencing choice of investigation modality away from colonoscopy. This behaviour is vindicated by the finding that LGI bleeding is less likely for inpatients with IDA. Conversely clinicians may be encouraged to undertake UGI endoscopy for inpatients following these results. Inpatients with IDA may represent a subset of inpatients more likely to benefit from acid suppression therapy, which could be a focus for future research.